Prediction of Aortic Stenosis Progression by 18F-FDG and 18F-NaF PET/CT in Different Aortic Valve Phenotypes - Patimat Murtazalieva; Darya Ryzhkova; Eduard Malev; Ekaterina Zhiduleva; Olga Moiseeva (Frontiers in Pharmacology, 2022)
Background: Different imaging techniques, such as echocardiography (ECHO) and CT, allow to assess aortic stenosis (AS) severity and could be used to study its progression. But only PET/CT open opportunities to assess activity of valvular inflammation and calcification in vivo. The aim of this study was to assess prognostic value of valvular inflammation and calcification measured by 18F-FDG and 18F-NaF PET/CT in patients with tricuspid (TAV) and bicuspid aortic valve (BAV).Methods: The study included 71 patients aged 40–70 years with mild, moderate and severe asymptomatic calcific AS. Patients were divided into two groups according to valve morphology: with BAV and TAV. All patients underwent standard ECHO, CT calcium scoring PET/CT with 18F-NaF and 18F-FDG. All patients were evaluated during a follow-up visit with evaluation of ECHO parameters. (16.8 ± 4.2 months).Results: TAV and BAV groups were comparable in AS severity by ECHO (peak aortic jet velocity (Vmax): 2.90 [2.60; 3.50] vs. 2.96 [2.55; 3.31] m/s, p = 0.83). TBR max 18F-FDG did not vary in TAV and BAV patients (1.15 [1.06; 1.23] vs. 1.11 [1.03; 1.20], p = 0.39). Both groups did not differ in valvular calcification degree (Agatston score 1,058 [440; 1798] vs. 1,128 [533; 2,360], p = 0.55) and calcification activity assessed by 18F-NaF uptake level (TBR max 1.50 [1.30; 1.78] vs. 1.48 [1.27; 1.83], p = 0.97). 18F-NaF TBR max was associated with AS severity measured by Vmax in men and women with TAV (r = 0.54; p = 0.04 vs. r = 0.53; p = 0.03). In BAV group this relationship was true only in female patients (r = 0.1; p = 0.67 vs. r = 0.7; p = 0.0004). There was no association between Vmax and TBR max 18F-FDG was revealed in TAV and BAV groups. During follow-up period, the most important positive predictors of AS progression in TAV obtained by multinomial logistic regression analysis were Vmax, and 18F-NaF TBR. Whereas in BAV the highest predictive value showed model included age and Vmax.Conclusion:18F-NaF PET/CT may be considered as the valuable predictor for hemodynamic progression of calcific AS in case of TAV. 18F-FDG PET/CT does not play a significant role to predict the AS progression.